Morita contexts and unitary ideals of rings - Kristo Väljako; Valdis Laan (Proceedings of the Estonian Academy of Sciences, 2021)
In this paper we study Morita contexts between rings without identity. We prove that if two associative rings are connected by a Morita context with surjective mappings, then these rings have isomorphic quantales of unitary ideals. We also show that the quotient rings by ideals that correspond to each other under that isomorphism are connected by a Morita context with surjective mappings. In addition, we consider how annihilators and two-sided socles behave under that isomorphism.